2003
DOI: 10.1002/cncr.11096
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of gastrointestinal involvement and its clinical significance in mantle cell lymphoma

Abstract: Emulsion polymers are “products by process” whose main properties are determined during polymerization. In this scenario of margins reduction, increasing competition, and public sensitivity to environmental issues, the challenge is to achieve an efficient production of high‐quality materials in a consistent, safe, and environmentally friendly way. This highlight reviews the investigations carried out at The University of the Basque Country to develop a knowledge‐based strategy to achieve these goals. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
154
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(178 citation statements)
references
References 61 publications
8
154
2
5
Order By: Relevance
“…Almost all MCL cases express cyclin D1 though, including the cases lacking CD5 (5% of the cases) or expressing CD23 (10% of the cases) [46]. GI tract involvement occurs frequently in MCL, typically in the form of multiple lymphomatous polyposis (MLP) [13]; and many consider MLP as the GI counterpart of MCL [47]. It is characterized by the presence of numerous polypoid lesions of malignant lymphoma, and is often accompanied by extraabdominal dissemination (especially to peripheral lymph nodes) [48].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Almost all MCL cases express cyclin D1 though, including the cases lacking CD5 (5% of the cases) or expressing CD23 (10% of the cases) [46]. GI tract involvement occurs frequently in MCL, typically in the form of multiple lymphomatous polyposis (MLP) [13]; and many consider MLP as the GI counterpart of MCL [47]. It is characterized by the presence of numerous polypoid lesions of malignant lymphoma, and is often accompanied by extraabdominal dissemination (especially to peripheral lymph nodes) [48].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In our case, the polypoid lesions in the duodenum were most probably MLP. Recent reports have endoscopically revealed that 46%-49% of MCL patients had esophago-gastroduodenal involvement, and that 38%-62% had colorectal involvement [10,13]. Endoscopic findings of the upper and lower GI tract in MCL have included inflammation, nodules, polyps, ulcers, thickened walls, and masses [13].…”
Section: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations